Formação de hexaluminato de cálcio in situ em refratários macroporosos: caminhos para o desenvolvimento de isolantes térmicos mais eficientes e ecológicos - Borges, Otávio Henrique (Universidade Federal de São Carlos, 2020)
Macroporous thermal insulators have recently emerged industrial interest due to their low thermal conductivity and toxicity compared to fiber-based insulators. Nonetheless, some challenges need to be overcome to enable a widespread application of this material. To face some of those, the effects of adding distinct Ca2+ sources and concentrations in alumina-based macroporous ceramics, were evaluated. Initially, the decrease of onset strengthening temperature (TS) induced by CaCO3 was investigated, and a likely mechanism to explain it was proposed. This mechanism allowed to infer that other Ca2+ sources, as Ca(OH)2 and CaO, would act similarly. This hypothesis was later confirmed. Additionally, reduction of shrinkage after firing were detected due to hibonite (CA6) formation induced by the presence of these Ca2+ sources. Ca(OH)2 and CaO could not be used in high concentrations without reducing the material porosity due to their effect on the ceramic suspension. However, this phenomenon was no observed for CaCO3, which could be used to produce an insulator with high porosity, linear expansion of 1% after firing at 1600ºC for 5h and thermal conductivity of 0.63Wm-1K-1 at 1200ºC. Finally, SiO2, TiO2 or ZnO in amounts varying from 0.6mol% to 2.8mol%, were evaluated as mineralizing agents. This analysis showed that the two latter allowed complete CA6 formation at, respectively, 1300ºC and 1400ºC rather than 1600ºC. Additionally, ZnO induced the development of CA6 with a higher aspect ratio without reducing the material's refractoriness. Thus, at the end of this work, it was possible to produce an in-situ macroporous thermal insulator comprised by acicular CA6 at 1300ºC, presenting high porosity (83%), zero shrinkage after firing at 1600ºC for 5h, TS of 680ºC and thermal conductivity of 0.55Wm-1K-1 at 1200ºC. Thereby, it is expected that the use of such material could help energy-intensive industries to improve their efficiency, reducing environmental impacts and production costs.
In situ formation of calcium hexaluminate in macroporous ceramics: routes for the development of more efficient and ecological thermal insulators
Keywords: Cerâmicas porosas; Hibonita; Fontes de Ca2+; Mineralizadores; Porous ceramics; Hibonite; Ca2+ sources; Mineralizing agents; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS